2021
DOI: 10.4085/1062-6050-0685.20
|View full text |Cite
|
Sign up to set email alerts
|

United States Air Force Academy Cadets' Unprompted Knowledge of Concussions and “Bell Ringers” or “Dings”: Perceived Differences and Similarities

Abstract: Context: After a potential concussion mechanism, a cadet is unlikely to have a list of concussion signs and symptoms at their disposal. As such, unprompted concussion knowledge may be an essential factor in personal recognition. Objective: The primary purpose of an overall study was to explore determinants that contributed to United States Air Force Academy (USAFA) cadets to disclose a concussion. This manuscript focuses on one of the eight overall themes discovered of unprompted concussion know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…A combination of vestibular/ocular, somatic, cognitive, and sleep symptoms were commonly noted via the free-response item. Findings are similar to previous research using samples of parents of youth athletes [22], college students [23], United States Air Force Academy cadets [25], and the general adult population [24], although specific proportions varied. As in those studies, our study found headache to be the most reported symptom in free response.…”
Section: Concussion Symptoms Identified By Free-response Itemsupporting
confidence: 85%
See 2 more Smart Citations
“…A combination of vestibular/ocular, somatic, cognitive, and sleep symptoms were commonly noted via the free-response item. Findings are similar to previous research using samples of parents of youth athletes [22], college students [23], United States Air Force Academy cadets [25], and the general adult population [24], although specific proportions varied. As in those studies, our study found headache to be the most reported symptom in free response.…”
Section: Concussion Symptoms Identified By Free-response Itemsupporting
confidence: 85%
“…Clinicians could consider adapting the simultaneous use of qualitative and quantitative symptom tracking methods (e.g., starting with questions focused on common symptoms, proceeding to use a checklist, and using re-sponses from each to highlight symptoms identified and missed). As discussed in previous research [25], although the use of colloquial terms is often not recommended, education provided by clinicians may benefit from using such terminology used by patients and their caregivers to help them better identify concussion symptoms and thus, respond accordingly (e.g., seeking care). However, it is necessary to note that utilizing qualitative concussion symptoms assessments may burden clinicians and may not translate to impactful clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation